Tradisi Jawa Mendhem Ari-Ari Dalam Studi Islam Di Boyolali Jawa Tengah - Uma Khasanah Khakim (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Indonesian culture is diverse and has a variety of cultural traditions, one of which is the Javanese tradition, namely mendhem ari-ari.. The tradition of mendhem ari-ari has been going on for a long time from generation to generation. Over time, Javanese culture has adapted to the mix of Islamic elements. In Boyolali for example, in teras, bendosari where the people there are strong in their Islamic teachings, but also still maintain previous Javanese traditions. This Mendhem ari-ari has been modified with Islamic elements, the relationship between culture and islam is visible before the mendhem ari-ari chats al fatihah 3x, al ikhlas 3x, al falaq 3x, an nas 3x which aims to protect the unborn baby from being disturbed by supernatural beings or harm, danger. Javanese anda Islamic culture in mendhem ari-ari is a social approach where this tradition develops in social society.